Kajian Teoritik Terhadap Modal Sosial Sebagai Basis Keterlibatan Masyarakat Dalam Pembangunan Pariwisata - Asep Rosadi (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2021)
Research and studies on the participation of a community in development programs, including tourism generally lead to the conclusion of the position and depth of the community in implementing development: is it still an object of development, has it been included them as the actors involved in planning, or has more deeply by taking part in the policy-making and management processes. This tendency to determine the position of involvement is only able to explain the position and/or performance of the community in the ladder of participation, participation spectrum, or type of participation, but cannot explain why a community group can be actively involved in development and others cannot. This paper is a theoretical study of the concept of social capital that can be used as an analytical tool to answer these questions. A sharper and more comprehensive understanding of this concept, academically and practically is needed to encourage tourism development at the community level.